2015
DOI: 10.1177/0193945915618610
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Yoga Interventions to Promote Cardiovascular Health in Older Adults

Abstract: The benefits of physical activity are well established, yet few older adults engage in adequate physical activity to optimize health. While yoga may reduce the risk of cardiovascular disease, few studies have focused on the efficacy of yoga-based physical activity to promote cardiovascular health in older adults. The objective of this review is to provide an evaluation of yoga interventions to reduce cardiovascular risk in older adults. Four databases were searched for randomized controlled trials of yoga inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…It is a mode of activity found to have multiple benefits for older adults [911]. Previous systematic reviews have provided evidence on the beneficial effects of yoga in older adults in terms of promoting cardiovascular health [12], balance and mobility [10], alleviating depression and improving quality of sleep [9]. A recent systematic review and meta-analysis by Tulloch et al [13] found that yoga had a medium effect on health related quality of life (HRQoL), and a small effect on mental wellbeing in people aged 60+ years.…”
Section: Introductionmentioning
confidence: 99%
“…It is a mode of activity found to have multiple benefits for older adults [911]. Previous systematic reviews have provided evidence on the beneficial effects of yoga in older adults in terms of promoting cardiovascular health [12], balance and mobility [10], alleviating depression and improving quality of sleep [9]. A recent systematic review and meta-analysis by Tulloch et al [13] found that yoga had a medium effect on health related quality of life (HRQoL), and a small effect on mental wellbeing in people aged 60+ years.…”
Section: Introductionmentioning
confidence: 99%
“…Yoga is an increasingly popular form of physical activity15 and refers to a unity of the body, mind and spirit 16. Recent research indicates beneficial effects of yoga on several health outcomes affecting elderly adults, including balance and mobility,17–19 cardiometabolic health,20–23 cognition,24–26 sleep quality and quality of life 27. Yoga practice has also been associated with better subjective well-being28–30 and improved mental health outcomes such as depression and anxiety 31 32.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence from recent studies has identified the elderly's interest in different type of physical activity that are simple, easy and help them in developing well-being and internal satisfaction than focused on fitness and appearances [13][14][15][16][17]. Well-being, which is consisted of physical, psychological and social components [18], and high well-being are associated with low prevalence of non communicable diseases, healthy aging and longevity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted across the globe have demonstrated the positive effects of yoga on the number of health outcomes that concerns elderly such as improvements in depression and anxiety [13,[23][24][25][26][27], mood and stress [25,28], pain reduction [29,30], enhanced sleep quality [13,25,26,30,31], balance resulting in fall prevention [23,27,32,33] cognition [31,34] and cardio metabolic health [17,28,30,35]. Studies have also reported improvement in the subjective well-being [36,37].…”
Section: Introductionmentioning
confidence: 99%